(untitled) (INNOTEC, 2013)
Hydrolysis of barley proteins into peptides and amino acids is one of the most important processes during barley germination.The degradation of the endosperm stored proteins facilitates water and enzyme movements, enhances modification, liberates starch granules and increases soluble amino nitrogen. Protease activity is the result of the activities of a mixture of exo- and endo-proteases. The barley proteins are initially solubilized by endo-proteases and the further by exo-proteases. Four classes of endo-proteases have been described: serine-proteases, cysteine-proteases, aspartic-proteases and metallo-proteases. The objective of this work was to develop a rapid and colorimetric enzymatic assay to determine the endo-proteolytic activity of the four endo-protease classes using two different substrates: azo-gelatin and azo-casein. Optimum conditions for the assays such as: pH,reaction time and temperature and absorbance scale were determined. Azo-gelatin presented several difficulties in standardizing an “in solution” assay. On the other hand, azo-casein allowed standardization of the assay for the four enzyme classes to produce consistent results. The endo-proteoteolytic method developed was applied to determine the endo-protease activity in barley, malt and wort.